EJERCICIO Nº 3

f ( x) = ( x 5 − 3 x 4 − x) ⋅ e − x

f ' ( x) = (5 x 4 − 12 x 3 − 1) · e − x + ( x 5 − 3 x 4 − x) · (−1) · e − x =
NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 3
f ( x) = ( x 5 − 3 x 4 − x) ⋅ e − x

f ' ( x) = (5 x 4 − 12 x 3 − 1) · e − x + ( x 5 − 3x 4 − x) · (−1) · e − x = (5 x 4 − 12 x 3 − 1 − x 5 + 3 x 4 + x) · e − x =
NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 3
f ( x) = ( x 5 − 3 x 4 − x) ⋅ e − x

f ' ( x) = (5 x 4 − 12 x 3 − 1) · e − x + ( x 5 − 3 x 4 − x) · (−1) · e − x = (5 x 4 − 12 x 3 − 1 − x 5 + 3 x 4 + x) · e − x = (− x 5 + 8 x 4 − 12 x 3 + x − 1) · e − x
SOLUCIÓN:

f ' ( x) = (− x 5 + 8 x 4 − 12 x 3 + x − 1) · e − x